Multicenter CT phantoms public dataset for radiomics reproducibility tests. Issue 3 (29th January 2019) - Kalendralis, Petros; Traverso, Alberto; Shi, Zhenwei; Zhovannik, Ivan; Monshouwer, René; Starmans, Martijn P. A.; Klein, Stefan; Pfaehler, Elisabeth; Boellaard, Ronald; Dekker, Andre; Wee, Leonard
Abstract : Purpose: The aim of this paper is to describe a public, open‐access, computed tomography (CT) phantom image set acquired at three centers and collected especially for radiomics reproducibility research. The dataset is useful to test radiomic features reproducibility with respect to various parameters, such as acquisition settings, scanners, and reconstruction algorithms. Acquisition and validation methods: Three phantoms were scanned in three independent institutions. Images of the following phantoms were acquired: Catphan 700 and COPDGene Phantom II (Phantom Laboratory, Greenwich, NY, USA), and the Triple modality 3D Abdominal Phantom (CIRS, Norfolk, VA, USA). Data were collected at three Dutch medical centers: MAASTRO Clinic (Maastricht, NL), Radboud University Medical Center (Nijmegen, NL), and University Medical Center Groningen (Groningen, NL) with scanners from two different manufacturers Siemens Healthcare and Philips Healthcare. The following acquisition parameter were varied in the phantom scans: slice thickness, reconstruction kernels, and tube current. Data format and usage notes: We made the dataset publically available on the Dutch instance of "Extensible Neuroimaging Archive Toolkit‐XNAT" (https://xnat.bmia.nl ). The dataset is freely available and reusable with attribution (Creative Commons 3.0 license). Potential applications: Our goal was to provide a findable, open‐access, annotated, and reusable CT phantom dataset for radiomics reproducibility studies. Reproducibility testing and harmonization are fundamental requirements for wide generalizability of radiomics‐based clinical prediction models. It is highly desirable to include only reproducible features into models, to be more assured of external validity across hitherto unseen contexts. In this view, phantom data from different centers represent a valuable source of information to exclude CT radiomic features that may already be unstable with respect to simplified structures and tightly controlled scan settings. The intended extension of our shared dataset is to include other modalities and phantoms with more realistic lesion simulations.